Review paperThe impact of ischemia-reperfusion injury on the effectiveness of primary angioplasty in ST-segment elevation myocardial infarction. - Araszkiewicz, Aleksander; Grygier, Marek; Lesiak, Maciej; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The most effective method of reperfusion in patients with ST-segment elevation myocardial infarction (STEMI) is primary percutaneous coronary intervention (PCI), assisted by aspiration thrombectomy and administration of antiplatelet agents and anticoagulants. However, effective restoration of blood flow in the infarct-related artery may paradoxically result in further damage to the heart muscle. This phenomenon, called ischemia-reperfusion injury (IRI), can significantly reduce the beneficial effects of reperfusion therapy. The rapid restoration of blood flow to the previously ischemic area causes a number of pathophysiological mechanisms leading to increased necrosis of myocytes still viable at the end of the ischemic period. It has been postulated that there are several strategies that can reduce damage to the heart muscle. Attempts to translate the results of experimental trials has been disappointing. More recently, however, some of the clinical benefits of ischemic postconditioning in which reperfusion in patients with STEMI who are undergoing PCI is interrupted with short episodes of ischemia were demonstrated. This renewed the interest in the reperfusion phase as a target for cardioprotective therapy. Research in this field has also been reinforced by the discovery of new potential targets for treatment that protects against IRI, such as the kinase pathway to protect against damage (reperfusion injury salvage kinases – RISK) and mitochondrial permeability transition pore. It seems that these findings will help to develop strategies that will improve the efficiency of mechanical reperfusion and may translate into long-term clinical effects.